The Political Philosophy of Impersonation: A Libertarian Analysis - Loo, Andy; Block, Walter (Journal of Law and Commerce, 2018)
Impersonation is a criminal act; it constitutes invasion and, in some cases, fraud. Although often associated with the term “identity theft,” impersonation is primarily a violation of the rights of the recipient of the communication, rather than that of the person being impersonated, whose rights are only sometimes violated. The present paper is devoted to defending this position. It attempts to overcome the objection that there is no violence necessarily connected to this act, or that the violence is directed toward the person being impersonated instead of the recipient of the impersonating message.